P‐174: 16.1‐times Elongation of Operation Lifetime in a Blue TTA‐OLED by using New ETL and EML Materials. Issue 1 (May 2017) - Lin, Bo-Yen; Lee, Ming-Zer; Tseng, Po-Chen; Lee, J. H.; Chiu, Tien-Lung; Lin, Chi-Feng; Hsieh, Julie; Chen, Stanley
Abstract : Elongation of operation lifetime in a blue TTA‐OLED was demonstrated with T90 increasing from 34 to 550 hours at the initial luminance of 2000 nits, corresponding to 16.1‐times improvement, by: 1. incorporation of new ETL material, 2. layer structure optimization, and 3. new EML material and double EML structures.